Uropathogens and Antibiotic Resistance Among Nursing Home Residents - National Healthcare Safety Network (NHSN). (4th October 2017) - Eure, Taniece; Stone, Nimalie D; Thompson, Nicola D; Bell, Jeneita; Mungai, Elisabeth
Abstract: Background: Knowledge of urinary tract infection (UTI) pathogen and susceptibility patterns is necessary to inform antibiotic prescribing and monitor resistance. We describe bacterial pathogens and UTI antibiotic resistance patterns among residents in nursing homes (NHs) reporting to the National Healthcare Safety Network (NHSN) long-term care facility (LTCF) component. Methods: All UTI events from January 1, 2013 to December 31, 2016 were included; up to three organisms per UTI event may be reported. Pathogen susceptibility results for selected antibiotics are reported as: Susceptible (S), Intermediate (I), Resistant (R), or Not tested (N). For this analysis, resistance was defined as I or R. We described pathogens and summarized antibiotic resistance only when ≥100 isolates of a bacterial species had susceptibility test results for a particular antibiotic reported to NHSN. Results: In 166 NHs located in 37 states, a total of 4, 054 pathogens were reported for 2, 827 residents. Six organisms accounted for 81% of all UTI events ( n  = 3, 599) (Table). A large proportion of Escherichia coli isolates, which accounted for 41% of uropathogens, were resistant to trimethoprim-sulfamethoxazole (35%) and levofloxacin (50%). Among Proteus mirabilis isolates, 53% were resistant to levofloxacin (Figure). Methicillin resistance was 74% among Staphylococcus aureus, and vancomycin resistance among Enterococcus spp. was 18%. Conclusion: This is the first summary of UTI pathogens and susceptibility data from U.S. nursing homes reporting to a national surveillance system. Resistance to antibiotics commonly used to treat UTIs was high. Tracking and preventing resistance for key pathogens is a CDC priority and NHSN reporting by NHs provides a crucial opportunity to track antibiotic resistance, highlighting the importance of enrolling more NHs into NHSN. Disclosures: All authors: No reported disclosures.